Responsive teaching orchestrating change - Abello, Larcy C. (UP Los Baños Journal, 2009)
This paper examined the realities of teaching reading in the public secondary schools. Data were elicited from 30 teachers-participants who attended and completed a one-week training course. The survey determined the status of teaching, the concerns and limitations, and the double measures deemed to make teaching and learning more responsive to the identified needs of students. The results suggest that there is a need for a collaborative effort involving teachers and administration and that although the teachers are not remains in their responsibilities to teach reading and employ appropriate teaching strategies to facilitate learning, there are disagreement and indecision regarding the following aspects: development of the teacher's own reading habits; putting up a mimi-library; use of reflective questioning; and explicit instruction of text features.